Livestock water use and productivity in the Nile Basin - Peden, Donald G. (Springer, 2010)
Livestock are the major consumers of water but also sustain millions of pastoralist and farming families. In regions where water is a scarce commodity, such as the Nile basin, there is a need for strategies to improve livestock water productivity (LWP). This study seeks to contribute to this need through a better understanding of livestock water use and productivity within the Nile basin and how this varies across the basin. We developed a spatial framework combining dynamic models of digestion in ruminants, crop water requirements (CWRs), and animal drinking water requirements to estimate spatial distribution of livestock water requirements in different livestock production systems (LPSs). We compared this with livestock production and water availability estimates within the basin. The results show that in most areas LWP is less than 0.1 USD/m3, with only few areas showing a LWP of 0.5 USD/m3 and higher. This is largely related to very low livestock meat and milk production on one hand and very variable, but, in general, low feed water productivity (fWP). Total water need for feed production was estimated to be roughly 94 billion m3, which amounts to approximately 5% of the total annual rainfall (68 billion m3 or 3.6% of total annual rainfall when excluding water for residues). Differences in LWP between systems and regions are large, suggesting considerable scope for improvements. We discuss the main factors influencing observed patterns of LWP and livestock water use and how this information can be used for developing strategies for increasing the water productivity of agricultural systems at the basin level.